1998
DOI: 10.1046/j.1365-2141.1998.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Desferioxamine increases iron depletion and apoptosis induced by ara‐C of human myeloid leukaemic cells

Abstract: Summary.We investigated whether changes in iron metabolism and the transferrin receptor (TRF-R) expression were involved in the antileukaemic effects of arabinoside cytosine (ara-C). Treatment with 100 nM ara-C for 48 h reduced thymidine uptake and increased the surface expression of the TRF-R on leukaemic blasts derived from 13/16 (81%) patients and on the HL-60 and U-937 cell lines. Whereas intracellular non-haem iron was strongly depleted 24 h after ara-C addition, TRF-R up-regulation and recovery of intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…Erythrocytes and plasma free iron levels were determined according to Leardi et al (1998) using a commercially available kit from Biomaghreb. Briefly, at acidic pH 4.8 all Fe 3+ released from transferrin were reduced by ascorbic acid into Fe 2+ , which constitutes with ferrozine a purple colourful complex measurable at 560 nm.…”
Section: Free Iron Determinationmentioning
confidence: 99%
“…Erythrocytes and plasma free iron levels were determined according to Leardi et al (1998) using a commercially available kit from Biomaghreb. Briefly, at acidic pH 4.8 all Fe 3+ released from transferrin were reduced by ascorbic acid into Fe 2+ , which constitutes with ferrozine a purple colourful complex measurable at 560 nm.…”
Section: Free Iron Determinationmentioning
confidence: 99%
“…Although it has been shown that DFB has a toxic effect on eukaryotic cells (Fukuchi et al 1994, Leardi et al 1998, we have demonstrated that this is not the case for our heterotrophic bioreporter (Fig. 5).…”
Section: Specificity Of Fe-siderophore Acquisition and Cross-utilizationmentioning
confidence: 78%
“…The interaction of TNK2 in vivo with clathrin and AP-2 participated in various trafficking pathways, underlying an ability to increase receptor-mediated transferrin uptake (37,39). It is well known that iron is essential for cell proliferation, and the iron was suggested to enhance the cell proliferation or anti-apoptotic effect (40)(41)(42)(43). The up-regulation of TNK2 and AP2B1 might induce the iron uptake into the leukemic cells, and the iron might play an important role for re-growth of the leukemic cells.…”
Section: Discussionmentioning
confidence: 99%